Overview of the Surgical Management of Liver Oligometastatic Disease in Colorectal Cancer - Anca Monica Oprescu Macovei; Dana Paula Venter; Bogdan Dumitriu; Constantin Oprescu; Mircea Dan Venter; Gabriel-Nicolae Andrei; Mures Sebastian Valcea Precup; Bogdan Socea; Mihai Stefan (Journal of Mind and Medical Sciences, 2025)
Oligometastatic colorectal cancer (CRC) refers to a state in which distant metastatic spread is limited to a few sites, offering the potential for curative treatment with aggressive local therapies. The surgical management of oligometastatic CRC has gained increasing attention due to its potential to improve survival. This review explores the evolving role of surgery in the treatment of oligometastatic disease, focusing on the criteria for selecting patients, surgical techniques, and outcomes. While systemic therapy remains essential, surgery can offer long-term survival benefits for appropriately selected patients with limited metastatic disease, particularly those with metastases confined to the liver. Advances in imaging technologies, minimally invasive surgical techniques, and perioperative care have enhanced the safety and efficacy of these procedures. The integration of multimodal therapies, such as chemotherapy, targeted therapy, and immunotherapy, in conjunction with surgery, is also discussed, with a focus on optimizing outcomes. To conclude, surgical resection of liver metastases improves survival compared to systemic therapy alone; thus, resection should be taken into consideration whenever possible. For initially unresectable diseases, personalized conversion therapy is indicated. This review aims to clarify how and when liver resection can first be chosen; when preoperative systemic treatment is needed; and if this is chosen, what is the best approach.